﻿Pengaruh Perputaran Kas dan Perputaran Piutang Terhadap Profitabilitas Pada Perusahaan Sektor Healthcare Yang Terdaftar di Bursa Efek Indonesia - Kusumawardani, Nistri (Universitas 17 Agustus 1945 Jakarta, 2025)
This study aims to analyze the effect of cash turnover and accounts receivable turnover on profitability in healthcare sector companies listed on the Indonesia Stock Exchange during the 2023-2024 period. The research sample consists of 19 companies selected using purposive sampling, with a total of 38 observations. The data used are annual financial statements, analyzed using multiple linear regression with E-Views 12 software. The results show that cash turnover has a positive and significant effect on profitability measured by Return on Assets (ROA). In contrast, accounts receivable turnover does not have a significant effect on profitability. These findings indicate that efficient cash management is a crucial factor in improving the profitability of healthcare companies, while the speed of accounts receivable collection does not significantly impact profitability during the study period. This study recommends that company management focus more on optimizing cash management to enhance financial performance.